Power, Provision and Punishment: Alfred’s Presentation of a King’s Responsibilities in the 'Old English Pastoral Care' and the 'Old English Boethius' - Masters, Samuel (2024)
Alfredian literature is at the forefront of early-medieval English (AngloSaxon) literary studies today. Scholars have largely been preoccupied with debating how much of the corpus is authentically Alfred’s and how much was composed by others under the king’s name. I shall address a more pertinent question: what do these texts reveal about Anglo Saxon expectations of kingship? Pratt argues Alfred’s translations present a rare depiction of an early-medieval king’s beliefs on ‘the source, distribution and uses of legitimate power’.